Pelatihan Penyusunan Best Practice dalam Penelitian Tindakan Kelas pada Guru SMP-SMA - Ira Eko Retnosasi; Tri Indrayanti; Agung Pramujiono; Henricus Supriyanto (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: The objectives of implementing community service include providing insight to teachers about best practice writing and providing best practice writing training. Method: The method used is field observation. The target in community service is junior-high school educators in Waru Sidoarjo district. These activities are carried out in the form of training activities, teaching, discussions, and research writing practices. Results: The training that has been carried out on middle-high school educators, namely (a) educators respond well to training in the PPM program, (b) educators have the motivation to improve in making scientific papers, (c) variety of scientific language is a common material in Indonesian language lessons so that educators are active in participating in training, (d) the teachers have a fairly good understanding in writing scientific papers, and (e) the educators respond well to aspects of the implementation of activities, aspects of the presenters, and aspects as a whole. Then, the final results show that from 44 participants, quantitatively that 30 participants have finished writing a best practice writing report, and only 14 participants still needed improvement. Conclusions: Through community service, teachers are able to make research through best practice. Although, there are some teachers who need revision related to the research content.